The significance of bunga terung tattoo for the Iban men In Julau, Sarawak and Putussibau Indonesia - Sonny Jumpo; Mohammad Puad Bebit (International Organization Center of Academic Research (OCERINT), 2021)
Bunga terung is a symbol synonymous with the Iban ethnic group in Borneo. This study is aimed to study the significance of bunga terung based on Ferdinand de Saussure’s Linguistic Unit comprising of Sign, Signified and Signifier. In Borneo, the bunga terung is worn by Iban men who have attained puberty to signify entry into adulthood. There are varying practices on the sequence of application of the bunga terung between the Iban of Sarawak and Kalimantan. An interesting observation regarding the sequence is the time the bunga terung is received. In Sarawak, the isi ginti (fish hook) tattoo is worn first – pre-puberty, followed by the bunga terung, and the pantang rekung leher (neck tattoo) before other tattoos for the back and the legs. In Kalimantan, the bunga terung is not worn if the Iban male has not gone berjalai. This study discusses two findings; the significance of the bunga terung; and the sequence of its application on the Iban men from Sarawak.